A self-monitored theranostic platform based on nanoparticle hyperthermia therapy and alternating magnetic field induced thermoacoustic imaging - Feng, Xiaohua (2015)
Low frequency alternating magnetic field (AMF) had been advocated for thermoacoustic imaging to exploit their inherent deeper penetrations. AMF induced thermoacoustic imaging of magnetic nanoparticles is particularly appealing since the system setup is inherently compatible with nanoparticle hyperthermia therapy. More importantly, owing to the capacity of thermoacoustics for accurate temperature measurement, the integration of AMF induced thermoacoustic imaging into nanoparticle hyperthermia therapy will potentially enable a theranostic platform with imaging guidance and temperature monitoring capabilities. We present herein the AMF induced thermoacoustic process of magnetic nanoparticles experimentally and then investigate furthermore its utilization in temperature monitoring for the nanoparticle hyperthermia. To demonstrate the concept of an integrated theranostic system with minimal overhead, a single coil is used for both the hyperthermia heating and thermoacoustic imaging by interleaving the two processes in time domain. In thermoacoustic imaging mode, the power is set at the amplifier's maximum value whereas to avoid excess heating of the coil in hyperthermia-mode, the power is switched to a lower value and the coil is further cooled by static water. Phantom imaging results of the magnetic nanoparticles and the self temperature monitoring with sub-degree accuracy during hyperthermia process are demonstrated. These proof-of-concept experiments showcase the potential to integrate thermoacoustic imaging with nanoparticle hyperthermia system. © (2015) COPYRIGHT Society of Photo-Optical Instrumentation Engineers (SPIE). Downloading of the abstract is permitted for personal use only.